Diversity of Anaerobic Methane Oxidizers in the Cold Seep Sediments of the Okinawa Trough - Chen, Ye; Xu, Cuiling; Wu, Nengyou; Sun, Zhilei; Liu, Changling; Zhen, Yu; Xin, Youzhi; Zhang, Xilin; Geng, Wei; Cao, Hong; Zhai, Bin; Li, Jing; et al. (Frontiers in Microbiology, 2022)
Active cold seeps in the Okinawa Trough (OT) have been widely identified, but the sediment microbial communities associated with these sites are still poorly understood. Here, we investigated the distribution and biomass of the microbial communities, particularly those associated with the anaerobic oxidation of methane (AOM), in sediments from an active cold seep in the mid-Okinawa Trough. Methane-oxidizing archaea, including ANME-1a, ANME-1b, ANME-2a/b, ANME-2c, and ANME-3, were detected in the OT cold seep sediments. Vertical stratification of anaerobic methanotrophic archaea (ANME) communities was observed in the following order: ANME-3, ANME-1a, and ANME-1b. In addition, the abundance of methyl coenzyme M reductase A (mcrA) genes corresponded to high levels of dissolved iron, suggesting that methane-metabolizing archaea might participate in iron reduction coupled to methane oxidation (Fe-AOM) in the OT cold seep. Furthermore, the relative abundance of ANME-1a was strongly related to the concentration of dissolved iron, indicating that ANME-1a is a key microbial player for Fe-AOM in the OT cold seep sediments. Co-occurrence analysis revealed that methane-metabolizing microbial communities were mainly associated with heterotrophic microorganisms, such as JS1, Bathy-1, and Bathy-15.